Rubber plantations and their implications on gender roles and relations in northern uplands Vietnam. Issue 11 (2nd November 2018) - Dao, Nga
Abstract: In recent years, rubber plantations have been strongly promoted in the northern uplands of Vietnam–especially in the northwest, where it is an ill agro-ecological fit–with an aim to improve ethnic minority livelihoods and to modernize peasants by transforming them into rubber workers. A large area of land has been taken away from farmers to make way for rubber plantations. This land acquisition and agrarian transformation have impacted local people and their livelihoods in various ways. Drawing on ethnographic research, in combination with interviews with authorities and studying related documents, this article focuses on the gendered consequences of rubber plantation in northern uplands Vietnam. It argues that the process of becoming a rubber worker and adapting to the new way of living has indeed added new roles and responsibilities for women. At the same time, it has undermined men's values and reshaped gender relations both within and outside the home.